2021
DOI: 10.1039/d1en00318f
|View full text |Cite
|
Sign up to set email alerts
|

Porous g-C3N4/TiO2 foam photocatalytic filter for treating NO indoor gas

Abstract: A g-C3N4/TiO2 heterojunction functional foams were constructed as gas purification filter for treating NO indoor gas with high removal rate (> 65 %) and high stability under visible-light (λ ≥...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In the case of C60-EDA/TiO2 nanocomposites, N1s appeared in the XPS spectrum (Figure 2c), providing further evidence to the successfully introduce C60-EDA into the composite, which was consistent with TEM-EDS mapping results. At the same time, it can be observed that the positive displacement of Ti 2p binding energy of C60-EDA/TiO2 relative to that of TiO2 is 0.4 eV (Figure 2d), indicating that there is an electronic interaction between C60-EDA and TiO2 [45]. It is worth noting that compared with pristine C60-EDA, the binding energies of N-Hx (401.7 eV) and C-N (399.5 eV) in the N1s high-resolution spectra of C60-EDA/TiO2 (Figure S5) are positively shifted by 1.1 and 0.4 eV, respectively, which should be caused by the formation of N-O-Ti by the interaction of the amino groups on C60-EDA with the hydroxyl groups on the surface of TiO2 [16].…”
Section: Morphology and Structure Characterizationmentioning
confidence: 81%
See 1 more Smart Citation
“…In the case of C60-EDA/TiO2 nanocomposites, N1s appeared in the XPS spectrum (Figure 2c), providing further evidence to the successfully introduce C60-EDA into the composite, which was consistent with TEM-EDS mapping results. At the same time, it can be observed that the positive displacement of Ti 2p binding energy of C60-EDA/TiO2 relative to that of TiO2 is 0.4 eV (Figure 2d), indicating that there is an electronic interaction between C60-EDA and TiO2 [45]. It is worth noting that compared with pristine C60-EDA, the binding energies of N-Hx (401.7 eV) and C-N (399.5 eV) in the N1s high-resolution spectra of C60-EDA/TiO2 (Figure S5) are positively shifted by 1.1 and 0.4 eV, respectively, which should be caused by the formation of N-O-Ti by the interaction of the amino groups on C60-EDA with the hydroxyl groups on the surface of TiO2 [16].…”
Section: Morphology and Structure Characterizationmentioning
confidence: 81%
“…To further elucidate the interaction of C60-EDA and TiO2, Raman and XPS experiments measurements were carried out. As shown in Figure 2b, the peaks of C60-EDA/TiO2 at 144, 400, 515, and 636 cm −1 are the characteristic peaks of anatase TiO2 with Eg(1), B1g(1), A1g(1), B1g(2), and Eg(2) vibration modes [17,44,45]. The fullerene-related Raman peaks appear between 1200-1600 cm −1 , which corresponds to the two typical peaks of C60-EDA (located at 1397 and 1579 cm −1 ), indicating the non-ignorable bond interaction between C60-EDA and TiO2 [17].…”
Section: Morphology and Structure Characterizationmentioning
confidence: 94%
“…Unlike calcination, the annealing reaction is carried out at a uniform cooling temperature on the basis of calcination. [77,78] In the fabrication of Co 3 O 4 QDs/g-C 3 N 4 , Zhang et al added Co 3 O 4 QDs suspension into ethanol solution dispersing g-C 3 N 4 . [78] Then the mixture was obtained by solvent evaporation with constant stirring at 100 °C and annealed at different temperatures (180, 250, 300 °C) in 2 h. Interestingly, the author pointed that the small pores were produced around Co 3 O 4 QDs, which indicated strong interactions between Co 3 O 4 QDs and g-C 3 N 4 .…”
Section: Calcination Methodsmentioning
confidence: 99%
“…In order to improve the removal of NO, Xiong et al suggested a combination of g-C 3 N 4 QDs with TiO 2 QDs using a pyrolysis process to construct a functional heterojunction foams filters, which displayed a higher photocatalytic activity for NO oxidation (65%). [77] The author pointed out that a large amount of NO was absorbed and a high light utilization efficiency was achieved on account of the large specific surface area and continuous pores in unique foams (Figure 20C,D). Moreover, all the samples possessed very low NO 2 concentration (<5 ppb) profiles during the photocatalytic NO oxidation process, successfully avoiding the harm of byproduct.…”
Section: No Oxidationmentioning
confidence: 99%
“…4). The photocatalytic house can participate in converting NO x gasses to nitrate anions, which are easily removed from the adsorbent surface of the photocatalyst by washing off (Nguyen et al 2020;Xiong et al 2021). Consequently, NO 3 − anions convert to ammonia via direct photocatalysis or electrochemical catalysis which may be renewably obtained from available and cheap photovoltaic panels (Hirakawa et al 2017;Li et al 2020).…”
Section: Sustainable Photocatalytic Housesmentioning
confidence: 99%